PEMBERDAYAAN KADER RT MELALUI LITERASI DIGITAL DAN PEMANFAATAN IT UNTUK MENINGKATKAN PELAYANAN PUBLIK DI DESA WANAGIRI, KECAMATAN SAKETI, PANDEGLANG - Samsinar Samsinar; Mohammad Syafrullah; Indah Suryawati; Dian Pita Sari; Syifa Fauziah Saputri (Jurnal Abdi Insani, 2025)
The Community Service Program in Wanagiri Village, Saketi Sub-district, Pandeglang, has been carried out successfully according to plan. The main focus of this activity is the use of information technology to improve the ability of village officials and neighborhood (RT) cadres to serve the community, as well as the development of a Village Website and a web-based Village Administration System application to provide broader access to information. Some RT cadres at the village level have already utilized information technology, and many villages have introduced ICT-based service innovations toward becoming digital villages. Wanagiri Village has pioneered the implementation of village administrative services by leveraging digital technology in the form of the Wanagiri Village Website and the Village Administration System (SADEWA). These two service innovations were created to enhance public services. Although both services have been established, the Wanagiri Village Administration System has not yet been fully implemented or further developed to achieve optimal performance, and the ability of RT cadres to operate this technology still needs to be strengthened. The community service activities were carried out through problem identification, website and administration system development, and supporting activities such as socialization, training, and mentoring. Despite these efforts, further intensive work is required to increase the capacity of village officials and RT cadres so that they gain a deeper understanding of digital literacy to support their productivity. The results of this program show improvements in digital skills, website content management, and community administrative services. The program contributes to realizing the vision of a model digital village that can be replicated in surrounding areas.